Distributed ledgers: Design and regulation of financial infrastructure and payment systems - Townsend, Robert M. (London The MIT Press, 2020)
Distributed ledger technology (DLT) has the potential to transform economic organization and financial structures. In this book, Robert Townsend steps back from the hype and controversy surrounding DLT (and the related, but not synonymous, innovations of blockchain and Bitcoin) to offer an economic analysis of what distributed ledgers can do and a blueprint for the optimal design and regulation of financial systems.